Exchange of Information and Data Protection in Cross-border Criminal Proceedings in Europe
XXVII, 491 p. 3 illus.
Keywords: In the past 10 years, the Member States of the European Union (EU) have intensified their exchange of information for the purposes of preventing and combating serious cross-border crime, as manifested in three main aspects. Firstly, there is a need to ensure the practical application of innovative principles (availability, mutual recognition) and concepts (Information Management Strategy, European Information Exchange Model) for tackling criminal organisations and networks that threaten the Internal Security of the EU. Secondly, there has been a gradual consolidation of EU agencies and bodies (Eurojust, Europol) aimed at promoting cooperation and dialogue among law enforcement officials and judicial authorities responsible for preventing and combating drug trafficking, trafficking in human beings, child pornography, and other serious trans-national offences. Thirdly, important EU information systems and databases (Prüm, SIS-II, ECRIS) have been created, enabling law enforcement and judicial authorities to gain access to essential information on criminal phenomena and organisations. Pursuing a practice-orientated approach, this work provides comprehensive coverage of all these measures, as well as the applicable rules governing data quality, data protection and data security. It is especially intended for law enforcement and judicial authorities who need to develop the appropriate expertise for the practical application of the above-mentioned principles. It also offers a solid basis of practical training material for police training centres and judicial schools.